Reflective Teaching and Epistemological Orientations among Early Childhood Educators in Pandemic Contexts: A Qualitative Study from Indonesia - Mayangsari, Dewi (Sinergi International Journal of Psychology, 2025)
This study aims to explore the epistemological beliefs and reflective practices of Early Childhood Education (ECE) teachers in Indonesia during the COVID-19 pandemic. This study uses a qualitative phenomenological approach with a semi-structured interview data collection method. Research participants were selected using a purposive sampling technique with the criteria of ECE teachers. Having at least three years of teaching experience and have taught at the Playgroup and Kindergarten levels, literate in using information technology, teach actively during the pandemic, active in self-development activities, and willing to be a research participant. There are two participants, IT and RA, who graduate from S1 level, Art Education and ECE. They teach in different schools and have teaching experience of thirteen and five years. The analysis was carried out with IPA (Interpretative Phenomenological Analysis), which resulted in the theme of the teaching process during a pandemic, teaching obstacles during a pandemic, factors that supported teaching during a pandemic, factors that hindered teaching during a pandemic, and beliefs in education during a pandemic based on their knowledge. The study results are that ECE teachers feel less confident about teaching during the pandemic because online learning is a new thing. They think that they don't have sufficient knowledge about online learning for early childhood education. They don't have the confidence to make sure that the students will understand, especially in the assessment process, which is believed to be a better face-to-face meeting.